К теории устойчивости композитных цилиндрических оболочек - Семенюк, Н.П.; Трач, В.М.; Жукова, Н.Б. (Прикладная механика, 2015)
Розроблено методику розрахунку стійкості шаруватих циліндричних оболонок з врахуванням анізотропії, що зумовлена наявністю в пакеті шарів з однією площиною симетрії. Розв’язувальну систему диференціальних рівнянь отримано на основі гіпотез Тимошенка в переміщеннях. Досліджено залежність критичних навантажень від напрямків армування моношарів, їх кількості, товщини, поперечної зсувної жорсткості при осьовому стиску. A technique of analysis of stability of the layered cylindrical shells is developed with allowance for anisotropy that is caused by presence in the layer package the layers with one plane of symmetry. The system of differential equations is obtained basing on Timoshenko hypotheses in displacements. A dependence of critical loads on directions of reinforcing the monolayers, their number, thickness, and is studied for the case of axial compression.